CUSTOMER SATISFACTION DETERMINATION AND IMPLICATIONS ON BEHAVIOR INTENTION (EMPIRICAL STUDY OF FOUR AND FIVE STAR HOTELS IN NORTH SULAWESI) - Noldy Paendong, Elim (Dinasti International Journal of Digital Business Management, 2021)
This study aims to determine and empirically prove the positive relationship between servicescape, interaction orientation, service convenience on customer satisfaction, and implications for behavior intention. This research problem departs from the concept of pentahelix in the tourism industry and the Ministry of Tourism's priority programs, especially digital tourism, and homestays are the central themes in this research. The success of achieving the target of tourist visits is closely related to the accommodation system at the destination, in this case the role of the hotel. On the other hand, the sustainability of a destination is closely related to the operations of the hotels located in that destination. That is, in conditions of an increase in the flow of visits to certain destinations accompanied by a rapid increase in the number of hotels. So it can be concluded that in a business both goods and services, servicescape, Interaction Orientation, Service Convenience are important factors in increasing customer satisfaction, even the three tadit factors, namely servicescape, interaction orientation, service convenience can encourage customer interest in using the product or services offered.